2011
DOI: 10.1111/j.1742-7843.2011.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B Alleles and Lamotrigine-Induced Cutaneous Adverse Drug Reactions in the Han Chinese Population

Abstract: Lamotrigine (LTG) is a commonly used antiepileptic drug. However, the use of LTG is limited because of its cutaneous adverse drug reactions (cADRs) ranging from mild maculopapular eruption (MPE) to severe Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). A strong association between HLA-B*1502 and carbamazepine-induced SJS ⁄ TEN has been identified in Chinese and Thai. Although three of seven cases with HLA-B*1502 have been reported in LTG-induced SJS ⁄ TEN so far, the relationship between H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…36 The protective mechanism of the introduction of small incremental doses, although not fully understood, is believed to involve the desensitisation of antigen presenting cells and T lymphocytes 37. Human leucocyte antigen (HLA) B genotyping may be useful in determining the predisposition to LTG-induced rash, but the level of HLA involvement is not fully determined 38. Comedication with valproic acid is also a significant predictor of rash in LTG-treated patients 33.…”
Section: Discussionmentioning
confidence: 99%
“…36 The protective mechanism of the introduction of small incremental doses, although not fully understood, is believed to involve the desensitisation of antigen presenting cells and T lymphocytes 37. Human leucocyte antigen (HLA) B genotyping may be useful in determining the predisposition to LTG-induced rash, but the level of HLA involvement is not fully determined 38. Comedication with valproic acid is also a significant predictor of rash in LTG-treated patients 33.…”
Section: Discussionmentioning
confidence: 99%
“…Studies into lamotrigine associated DHS however, have produced conflicting results. Several studies could not show a link between lamotrigine-induced SJS and the carriage of HLA-B*1502 in the Han Chinese [66,67]. Others, which have examined oxcarbazepine-, phenytoin-and lamotrigine-induced SJS/TEN together, have reported expression of HLA-B*1502 in 33% of lamotrigine SJS cases, yet the reported differences from controls did not reach statistical significance [64].…”
Section: Cbzmentioning
confidence: 97%
“…However, studies linking HLA-B*15:02 with oxcarbazepine-induced SJS or MPE have shown mixed results [131, 146-148]. Though no individual studies have found significant associations between *15:02 and lamotrigine-induced adverse reactions [130, 131, 149, 150], a meta-analysis of four studies did find a significantly increased risk for SJS/TEN for patients carrying *15:02 who receive lamotrigine [118]. …”
Section: Important Variantsmentioning
confidence: 99%